Isolation of a laminin-binding protein from muscle cell membranes - Lesot, Herve (1983)
Skeletal muscle myofibers are each ensheathed by a continuous basal lamina consisting predominantly of type IV collagen, laminin and heparan sulfate proteoglycan. In order to identify laminin-binding components in the muscle cell surface, plasma membranes from mouse thigh muscle and from rat L6 myoblasts were separated by polyacrylamide gel electrophoresis and transferred to nitrocellulose paper by electroblotting. Incubation of the transferred samples with (125)I-labelled laminin revealed a prominent band of approximate mol. wt. 68 000. A protein of this mol. wt. was isolated by affinity chromatography of muscle cell plasma membranes on laminin-Sepharose. The hydrophobic protein has an apparent mol. wt. of 68 000 and has a high content of serine, glycine and acidic amino acids. After detergent solubilization the purified protein binds to laminin-coated Sepharose beads at a higher rate than to beads coated with either fibronectin or collagen types I and IV. The interaction of the protein, called LB 68, with laminin was also studied after incorporation into synthetic lecithin vesicles. While detergent-solubilized LB 68 bound to (125)I-labeled laminin only at lower than physiological ionic strength, liposome-incorporated LB 68 bound to laminin in the absence of detergents under physiological conditions. We propose that this protein is involved in the interaction of myoblasts with laminin substrates and thus may participate in the anchorage of the basal lamina in the plasmalemma of myotubes.